Green : the beginning and the end - Dekker, Ted, 1962- (Nashville, Tenn. : Thomas Nelson, 2009)
The story of how Thomas Hunter first entered the Black Forest and forever changed history begins at a time when armies were gathered for a final battle in the valley of Migdon. Prequel to "Black" and sequel to "White."
Keywords: Hunter, Thomas (Fictitious character) -- Fiction; Dreams -- Fiction; Reality -- Fiction; Christian -- Fiction; Fantasy -- Fiction; Fantasy fiction; Christian fiction; Fantasy fiction; Christian fiction